DYNAMIC RELIABILITY ANALYSIS OF PHOTOVOLTAIC SUPPORT SYSTEM CONSIDERING MULTIPLE UNCERTAINTIES - ZHONG Wei; YANG HuanHong; MA XiangDong; HUANG LongAn (Jixie qiangdu)
Dynamic reliability analysis method of photovoltaic support system(PSS)was proposed considering the multiple uncertainties.Firstly,the reliability analysis model of PSS was constructed based on the probability density evolution method(PDEM),including the probability conservation equation,basic governing equation and density evolution equation.Then,the finite element analysis model of PSS was built,including the structural stress model,load combination form,and mesh generation algorithm.In simulation,the randomness in load combination and structures were incorporated,in which consists of six basic random parameters and 44 representative systems.The solution efficiency was improved by the joint simulation of PDEM and Abaqus.Results show that stress and displacement are two failure modes of PSS,and the influence of the latter is more obvious.The reliability index under the basic load combination condition is 0.928.As wind speed increases,the structural reliability decreases.In the high⁃speed range larger than 40 m/s,the uncertainty in structure itself will overestimate the reliability level of PSS,which should be paid attention in design.